Epileptic auditory illusions as reliable findings in the determination of the lateralization and localization of epileptogenic zone - Balgetir, Ferhat; Mungen, Bulent; Gonen, Murat; Mungen, Eren; Tasci, Irem (Academic Press Inc Elsevier Science, 2018)
Aim: The aim of this study was to investigate the types and prevalence of epileptic auditory auras (EAA) in a large population with epilepsy based on a clinical analysis, to analyze the relationship between auditory auras and the hemispheric lateralization/localization of the epileptogenic zone, and to determine whether there is a reliable EM that could be used for the identification of the localization and lateralization of the epileptogenic zone. Methods: The retrospective study included 1050 patients with a diagnosis of epilepsy, including 854 (8133%) patients with focal epilepsy and 196 (18.67%) with generalized epilepsy. Medical records of 72 patients with auditory auras were singled out, and 63 of them were included in the study. The auditory auras were classified based on their clinical characteristics, and an analysis was performed to examine the relation of the type of auditory auras with the hemispheric lateralization/localization of the epileptogenic zone. Additionally, further analyses were performed to investigate whether there can be a reliable EAA that could be used for the identification of the localization and lateralization of the epileptogenic zone. Results: Of the 1050 patients with a diagnosis of epilepsy, 63 cases of EAA were included in the study. The prevalence of EAA was 6% in the population with generalized epilepsy and 7.38% in the patients with focal epilepsy. Of the 63 patients, 58 (92.06%) were right-hand-dominant, and 5 (7.94%) were left-hand-dominant. The epileptogenic zone was mostly localized to the temporal lobe (n = 56: 88.89%). In all the 12 patients that had isolated auditory illusion or auditory illusion - elementary or complex auditory hallucinations, the epileptogenic zone was lateralized to the dominant hemisphere and even localized to the temporal lobe of the dominant hemisphere. Significance: The prevalence of EM in the population with generalized epilepsy can be found higher than expected if a detailed evaluation of the population with generalized epilepsy can be performed, as in specific patient groups. Our results indicated that the epileptogenic zone was lateralized to the dominant hemisphere in all the patients with isolated auditory illusion or auditory illusion elementary or complex auditory hallucinations, which suggests that auditory illusion can be a reliable tool in the determination of the lateralization and even localization of the epileptogenic zone. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Aura; Auditory illusion; lateralization